Multiple Mechanisms Regulate Eukaryotic Cytochrome C Oxidase - Rabia Ramzan; Bernhard Kadenbach; Sebastian Vogt (Cells, 2021)
Cytochrome c oxidase (COX), the rate-limiting enzyme of mitochondrial respiration, is regulated by various mechanisms. Its regulation by ATP (adenosine triphosphate) appears of particular importance, since it evolved early during evolution and is still found in cyanobacteria, but not in other bacteria. Therefore the “allosteric ATP inhibition of COX” is described here in more detail. Most regulatory properties of COX are related to “supernumerary” subunits, which are largely absent in bacterial COX. The “allosteric ATP inhibition of COX” was also recently described in intact isolated rat heart mitochondria.